Anesthetic Considerations for the Parturient After Solid Organ Transplantation. (August 2016) - Moaveni, Daria M.; Cohn, Jennifer H.; Hoctor, Katherine G.; Longman, Ryan E.; Ranasinghe, J. Sudharma
Abstract : Over the past 40 years, the success of organ transplantation has increased such that female solid organ transplant recipients are able to conceive and carry pregnancies successfully to term. Anesthesiologists are faced with the challenge of providing anesthesia care to these high-risk obstetric patients in the peripartum period. Anesthetic considerations include the effects of the physiologic changes of pregnancy on the transplanted organ, graft function in the peripartum period, and the maternal side effects and drug interactions of immunosuppressive agents. These women are at an increased risk of comorbidities and obstetric complications. Anesthetic management should consider the important task of protecting graft function. Optimal care of a woman with a transplanted solid organ involves management by a multidisciplinary team. In this focused review article, we review the anesthetic management of pregnant patients with solid organ transplants of the kidney, liver, heart, or lung. Abstract : Published ahead of print June 9, 2016